Exposure to violence, a risk for suicide in youths and young adults. A meta‐analysis of longitudinal studies. (20th December 2016) - Castellví, P.; Miranda‐Mendizábal, A.; Parés‐Badell, O.; Almenara, J.; Alonso, I.; Blasco, M. J.; Cebrià, A.; Gabilondo, A.; Gili, M.; Lagares, C.; Piqueras, J. A.; Roca, M.; et al.
Abstract : Objective: To assess the association and magnitude of the effect of early exposure to different types of interpersonal violence (IPV) with suicide attempt and suicide death in youths and young adults. Method: We searched six databases until June 2015. Inclusion criteria were as follows: (1) assessment of any type of IPV as risk factor of suicide attempt or suicide: (i) child maltreatment [childhood physical, sexual, emotional abuse, neglect], (ii) bullying, (iii) dating violence, and (iv) community violence; (2) population‐based case–control or cohort studies; and (3) subjects aged 12–26 years. Random models were used for meta‐analyses (Reg: CRD42013005775). Results: From 23 682 articles, 29 articles with 143 730 subjects for meta‐analyses were included. For victims of any IPV, OR of subsequent suicide attempt was 1.99 (95% CI: 1.73–2.28); for child maltreatment, 2.25 (95% CI: 1.85–2.73); for bullying, 2.39 (95% CI: 1.89–3.01); for dating violence, 1.65 (95% CI: 1.40–1.94); and for community violence, 1.48 (95% CI: 1.16–1.87). Young victims of IPV had an OR of suicide death of 10.57 (95% CI: 4.46–25.07). Conclusion: Early exposure to IPV confers a risk of suicide attempts and particularly suicide death in youths and young adults. Future research should address the effectiveness of preventing and detecting early any type of IPV exposure in early ages.